An introduction to integral transforms - Patra, Baidyanath (Boca Raton, Fla. : CRC Press, 2018)
"'An Introduction to Integral Transforms' is meant for students pursuing graduate and post graduate studies in Science and Engineering. It contains discussions on almost all transforms for normal users of the subject. The content of the book is explained from a rudimentary stand point to an advanced level for convenience of its readers. Pre'requisite for understanding the subject matter of the book is some knowledge on the complex variable techniques.Please note: Taylor & Francis does not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka."--Provided by publisher.
chapter 1 Fourier Transform / Baidyanath Patra -- chapter 2 Finite fourier transform / Baidyanath Patra -- chapter 3 The laplace transform / Baidyanath Patra -- chapter 4 The Inverse Laplace Transform and Application of Laplace Transform / Baidyanath Patra -- chapter 5 Hilbert and Stieltjes Transforms / Baidyanath Patra -- chapter 6 Hankel Transforms / Baidyanath Patra -- chapter 7 Finite Hankel Transforms / Baidyanath Patra -- chapter 8 The Mellin Transform / Baidyanath Patra -- chapter 9 Finite laplace transforms / Baidyanath Patra -- chapter 10 Legendre transforms / Baidyanath Patra -- chapter 11 The Kontorovich-Lebedev Transform / Baidyanath Patra -- chapter 12 The Mehler-Fock Transform / Baidyanath Patra -- chapter 13 Jacobi, Gegenbauer, Laguerre and Hermite Transforms / Baidyanath Patra -- chapter 14 The Z-Transform / Baidyanath Patra.
Keywords: Integral transforms